S/Z in the Hispanic Context: Castration and Otherness in the Female Characters of Miguel de Cervantes and María de Zayas - Montauban, Jannine (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2021)
In S/Z (1970), an ambitious semiotic study of Honoré de Balzac’s “Sarrasine,” Roland Barthes analyzes the ideological oppositions behind this graphic differentiation based on observing an unexpected deviation from the norm in the male protagonist’s name. This article reveals that Barthes’s analysis is applicable to Cervantes’s and Zayas’s novellas, abounding as they are in female Moorish characters whose names begin with the letter Z. The presence of this Z is best understood, not in phonological terms, but from the perspective of the cultural fabric of seventeenth-century Spain, where the Z becomes the stamp that unequivocally denounces the otherness and social castration of the female characters.